2014
DOI: 10.1002/pc.22845
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo fabric reinforced polypropylene and poly(lactic acid) for packaging applications: Impact, thermal, and physical properties

Abstract: The main objective of this study is to explore the potential of using totally green composites made from renewable resources in packaging applications as compared to conventional thermoplastics. In this work, we undertook a comparative study of the functional properties related to the packaging applications of bamboo fabric–Polypropylene (PP) and bamboo fabric–Poly(lactic acid) (PLA) composites. Results indicate that Charpy impact strength was increased from 37.5 to 126 J/m for bamboo fabric–PLA composites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…We observed that the impact strength of all of the composites were higher than those of the neat PLA, regardless of the treatment type. This finding was parallel to findings the literature . The highest impact strength was obtained in the silanized and polymer‐coated flax fiber composites.…”
Section: Resultssupporting
confidence: 89%
“…We observed that the impact strength of all of the composites were higher than those of the neat PLA, regardless of the treatment type. This finding was parallel to findings the literature . The highest impact strength was obtained in the silanized and polymer‐coated flax fiber composites.…”
Section: Resultssupporting
confidence: 89%
“…Sisal, hemp and flax fibres are examples of commonly used for interior door padding, floor panels and linings for seatbacks [11]. This is mainly to serves a twofold goal of the companies; (1) to lower the overall weight of the vehicle, hence improving fuel efficiency and (2) to ensure the sustainability in the manufacturing process [11].…”
Section: Introductionmentioning
confidence: 98%
“…This is mainly due to the fact that the sustainability issue of the synthetic fibre reinforcements is yet to be solved despite their predominant performance for mechanical and other functional properties. Until recently, extensive studies on natural fibres and their hybrids, such as bamboo [1,2], flax [3][4][5][6][7], sisal [8], and jute [9] have proved the potential of these fibres to be effective reinforcement for composite materials. In this context, physical and chemical treatments of these lignocellulose fibres have been attempted to further improve some important properties such as wettability and fibre-matrix compatibility or adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been widely used in its natural form for light‐framed constructions and furniture or as fiber feedstock for pulp and paper . Besides, it can be also used to produce bamboo fiber reinforced composites (BFC), which have been finding extensive applications spanning from decorating materials to constructions for their excellent physico‐mechanical performances and low threaten to environment .…”
Section: Introductionmentioning
confidence: 99%